Ofsted: Curriculum impact. (2nd May 2021) - Bromley, Matt
Abstract : As part of Ofsted's focus on curriculum impact, evaluating the pace of pupil progress, pupil outcomes, and their preparedness for their next steps are vital considerations – as is the 'performance development' of teachers. Matt Bromley advises